Influence of post-warm-up recovery time on swim performance in international swimmers - West, D. J.; Dietzig, B. M.; Bracken, R. M.; Cunningham, D. J.; Crewther, B. T.; Cook, C. J.; Kilduff, L. P. (Journal of Science and Medicine in Sport, 2013)
Swimmers must enter a marshalling call-room 20 min prior to racing, which results in some swimmers completing their warm-up 45 min pre-race. Since a recovery period longer than 15-20 min may prove problematic, this study examined 200 m freestyle performance after a 20 and 45 min post-warm-up recovery period.